Effect Of WC Grain Size On The Binder Corrosion Behaviour Of WC-Co Cemented Carbide In Acidic, Neutral And Alkaline Media - Cinca, Núria; Peres, Riberto Nunes [UNESP]; Tarrés, Elena; Lavigne, Olivier; Benedetti, Assis Vicente [UNESP] (European Powder Metallurgy Association, 2023)
The effect of the WC grain size on the corrosion resistance of cemented carbides is not well established in the literature. In this study, the electrochemical behaviour of WC-12wt.%Co hard materials with various starting grain sizes (ultrafine, fine, and medium) were evaluated in aerated 3.5 wt.% NaCl media as well as 0.1M NaOH and 0.1M H2SO4, by means of electrochemical techniques (Electrochemical Impedance Spectroscopy, EIS, and polarization scans). Results showed that the corrosion resistance of the material is slightly dependant on the WC grain size. Based on EIS results, the corrosion resistance of the material in acidic media slightly increases when decreasing the WC grain size, while an inverse trend is observed in alkaline media. This is due to the inherent heterogeneity of the two-phase nature of these materials.